2013
DOI: 10.1111/ajt.12424
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Molecular Characterization of Bacteremia Due to Carbapenem-Resistant Klebsiella pneumoniae in Transplant Recipients

Abstract: We conducted a retrospective study of 17 transplant recipients with carbapenem-resistant Klebsiella pneumoniae bacteremia, and described epidemiology, clinical characteristics and strain genotypes. Eighty-eight percent (15/17) of patients were liver or intestinal transplant recipients. Outcomes were death due to septic shock (18%), cure (24%) and persistent (>7 days) or recurrent bacteremia (29% each). Thirty- and 90-day mortality was 18% and 47%, respectively. Patients who were cured received at least one act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
101
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 38 publications
2
101
2
1
Order By: Relevance
“…ETP MICs appear to be bimodally distributed in K. pneumoniae, and this seems to correlate with defects and variations in OmpK36, as previously reported in association with KPC-producing isolates, and with ESBL and AmpC-type ␤-lactamases (8,40,55,56). We found a large diversity of OmpK36 defects in our set of ETP-resistant K. pneumoniae isolates, all of which were reported previously: frameshift mutations (43), IS (57), a premature stop codon (58,59), and a GD duplication in loop 3 (44,45,60). OmpK36 was detected by SDS-PAGE only in those isolates with the GD duplication.…”
Section: Discussionsupporting
confidence: 86%
“…ETP MICs appear to be bimodally distributed in K. pneumoniae, and this seems to correlate with defects and variations in OmpK36, as previously reported in association with KPC-producing isolates, and with ESBL and AmpC-type ␤-lactamases (8,40,55,56). We found a large diversity of OmpK36 defects in our set of ETP-resistant K. pneumoniae isolates, all of which were reported previously: frameshift mutations (43), IS (57), a premature stop codon (58,59), and a GD duplication in loop 3 (44,45,60). OmpK36 was detected by SDS-PAGE only in those isolates with the GD duplication.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, ST258 strains were distinct by genotypes (presence of particular molecular mechanisms of antimicrobial resistance) and/or phenotypes (antimicrobial susceptibility profiles). Our data add to a growing body of evidence that ST258 K. pneumoniae strains are highly heterogenous, despite being considered clonal by conventional molecular epidemiologic criteria (5,(26)(27)(28)(29)(30). We previously showed that differences in ompK36 genotypes and gene expression among ST258 strains at our center predict susceptibility or resistance to carbapenemcolistin combinations during time-kill assays (27,29).…”
Section: Discussionmentioning
confidence: 51%
“…We previously showed that differences in ompK36 genotypes and gene expression among ST258 strains at our center predict susceptibility or resistance to carbapenemcolistin combinations during time-kill assays (27,29). Recent studies from our group and others have demonstrated striking diversity in the core genome of ST258 K. pneumoniae strains, including strains recovered from patients at single centers or longitudinally from the bloodstreams of individual patients (26,28). Variations in plasmid content and number are associated with differences in multidrug resistance patterns (26).…”
Section: Discussionmentioning
confidence: 91%
“…19 The incidence of post-SOT CRKP infection varies considerably by center and type of transplant (Table 1). [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In general, CRKP infections occur early after transplant, with most studies reporting a median time of <50 days from transplant to infection. Reported mortality rates among SOT recipients with CRE infection generally range from 30-50%, and post-transplant CRKP infections have been associated with as much as a 10-fold risk of death.…”
mentioning
confidence: 99%
“…Reported mortality rates among SOT recipients with CRE infection generally range from 30-50%, and post-transplant CRKP infections have been associated with as much as a 10-fold risk of death. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] However, a more recent cohort of 164 SOT recipients across 15 international sites confirmed that while CRE infection typically occurs in the early post-transplant period, the one-year survival rate of patients who developed CRE infection within the first year of transplant was 72%. 34 While CRKP infections remain the most common type of CRE infection in SOT recipients, infections due to carbapenem-resistant Enterobacter spp., as well as NDM-and OXA-48-producing K. pneumoniae have also been reported.…”
mentioning
confidence: 99%